METHODOLOGICAL APPROACHES TO THE APPLICATION OF STEAM EDUCATION TECHNOLOGIES - Alimova Feruza Askarjanovna (International Journal of Literature and Language Studies, 2026)
The rapid evolution of educational technologies has accelerated the adoption of interdisciplinary teaching approaches that prepare learners for the challenges of the twenty-first century. Among these approaches, STEAM education, which integrates Science, Technology, Engineering, Arts, and Mathematics, has become an effective methodology for developing students’ creativity, critical thinking, collaboration, communication, and problem-solving skills. This study examines the methodological approaches to the application of STEAM education technologies and evaluates their effectiveness in improving teaching quality and student learning outcomes. The research analyzes the principles of project-based learning, inquiry-based instruction, interdisciplinary curriculum integration, and technology-enhanced learning environments supported by digital tools such as robotics, virtual laboratories, simulation software, programming platforms, and engineering design applications. The findings indicate that the proposed methodology significantly improves student engagement, academic achievement, digital literacy, creativity, collaborative learning, and innovation while strengthening teachers’ instructional effectiveness and interdisciplinary cooperation. The study also identifies several challenges associated with STEAM implementation, including teacher professional development, technological infrastructure, curriculum integration, and competency-based assessment. The proposed methodological framework provides practical recommendations for the sustainable integration of STEAM education technologies into modern educational systems. Overall, the study concludes that STEAM education represents an effective pedagogical model for preparing students with the interdisciplinary knowledge, practical competencies, and innovative thinking required for future academic, professional, and societal development.